VERIFICATION OF THE PHYSICAL AND MATHEMATICAL MODEL FOR CALCULATION OF AERODYNAMIC CHARACTERISTICS OF BLUFF BODIES MOVING IN AIR AT LARGE MACH NUMBERS - A. D. Chorny; A. N. Chichko; Yu. V. Zhukova; I. G. Kukharchuk; A. F. Melets; V. A. Malkin (Системный анализ и прикладная информатика)
The verification results of the computer simulation model for calculation of aerodynamic characteristics of bluff bodies (cone with different apex angles and a «cone–cylinder» body) moving in air at different Mach number and zero angle of attack are presented. It is shown that numerical simulation results fairly agree with physical experiment data.